Production and fixation of flowers and pods in three soybean cultivars - Marchezan, Enio; Costa, José Antonio (Pesquisa Agropecuaria Brasileira, 2014)
Reproductive activity of the soybean (Glycine mar (L.) Merrill) cultivars Planalto, Br-4 and Sulina, subjected to conditions for high yield, was evaluated during 1980/81 at the Estação Experimental Agronômica da Universidade Federal do Rio Grande do Sul, Guaíba, RS. The characterization of the reproductive activity was performed by node, counting flowers and pods produced and pods fixed, both in the main stem and branches. There were no differences in flowers and pods produced and pods fixed by plant, that in the average of the three cultivars was of 199,102 e 33, respectively. Branches contributed with 66% of the seed yield. Nodes number six, seven, eight and nine, counted beginning with the unifoliolate node, had the highest number of flowers and pods produced and fixed.